On the usefulness of government spending in the EU area - Luigi Marattin; Simone Salotti (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2009)
We investigate the effects of fiscal policy on private consumption and investment in the European Union. A certain consensus has aroused that fiscal impulses have expansionary Keynesian effects on the economic activity. However, the existing empirical literature has concentrated on few countries, mostly outside the EU. We check the validity of this result for the EU area, by using annual data and a panel vector auto-regression approach (PVAR). Our results show that increases in public spending lead to positive and significant effects on private consumption and private investment. According to our baseline estimate, a 1% increase in public spending produces a 0.36% on impact rise in private consumption, and a 0.79% impact rise in private investment. The effects are substantial, and die out slowly (faster in the case of private consumption). A further disaggregation between wage and non-wage components reveals different effects. As for the impact on private consumption, our results show that public salaries have a relatively stronger stimulating role, a result which is probably due to the importance of the public sector especially in continental Europe. On the other hand, the positive impact on private investment is mainly due to the non-wage component of government consumption.
Keywords: E62; C33; 330